CORAL RECRUITMENT ONTO CONCRETE ARTIFICIAL REEF IN HARI ISLAND, SOUTHEAST SULAWESI - Subhan, Subhan; Pratikino, Asrin Ginong (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2017)
Study on coral recruitment in artiﬁcial reefs was carried out in Hari Island, Southeast Sulawesi. Data collection was conducted by calculating the number of genus colony and measuring coral size using visual census method equipped with scuba diving and an underwater camera. The construction of artiﬁcial reefs would vertically expand the proﬁle of the survival of juvenile coral recruitment, where 95 new colonies of the recruitment had successfully been observed. Moreover, there were 10 genus of stony coral (Scleractinia) managed to be identiﬁed with the abundance proportion of Pocillopora, Acropora, Fungis, Leptoseris, Cynarina, Seriotopora, Acanthastrea, Favites, Montipora, Oxypora. The entire coral recruitment was dominated by genus Pocillopora reaching 80.0%. The coral recruitment in artiﬁcial reefs showed that there was potential coral recovery in the island.